Answer:
Yes, it will reach or exceed 141 degree F
Step-by-step explanation:
Given equation that shows the temperature T in degrees Fahrenheit x minutes after the machine is put into operation is,
![T = 0.005x^2 + 0.45x + 125](https://tex.z-dn.net/?f=T%20%3D%200.005x%5E2%20%2B%200.45x%20%2B%20125)
Suppose T = 141°F,
![\implies 141 = 0.005x^2 + 0.45x + 125](https://tex.z-dn.net/?f=%5Cimplies%20141%20%3D%200.005x%5E2%20%2B%200.45x%20%2B%20125)
![\implies 0.005x^2 + 0.45x + 125 - 141 =0](https://tex.z-dn.net/?f=%5Cimplies%200.005x%5E2%20%2B%200.45x%20%2B%20125%20-%20141%20%3D0)
![\implies 0.005x^2 + 0.45x - 16=0](https://tex.z-dn.net/?f=%5Cimplies%200.005x%5E2%20%2B%200.45x%20-%2016%3D0)
Since, a quadratic equation
has,
Real roots,
If Discriminant, ![D = b^2 - 4ac \geq 0](https://tex.z-dn.net/?f=D%20%3D%20b%5E2%20-%204ac%20%5Cgeq%200)
Imaginary roots,
If D < 0,
Since, ![0.45^2 - 4\times 0.005\times -16 = 0.2025 + 32 > 0](https://tex.z-dn.net/?f=0.45%5E2%20-%204%5Ctimes%200.005%5Ctimes%20-16%20%3D%200.2025%20%2B%2032%20%3E%200)
Thus, roots of -0.005x² + 0.45x + 125 are real.
Hence, the temperature can reach or exceed 141 degree F.
Answer:
1. 24.36
2. Do the same thing (follow the steps in the picture)
Step-by-step explanation:
Answer:
5 months
Step-by-step explanation:
To solve this problem, we need to create and algebraic equation for when Jill's weight will be equal to Paris's. If we take their current weight and then add the additional weight gain per month times the number of months, we can calculate the amount of time it will take for their weight to be equal by solving for m.
![120+10m=150+4m\\10m-4m=150-120\\6m=30\\m=5](https://tex.z-dn.net/?f=120%2B10m%3D150%2B4m%5C%5C10m-4m%3D150-120%5C%5C6m%3D30%5C%5Cm%3D5)
Answer:
19 mm
Step-by-step explanation:
A penny is not that large, and you can fit multiple pennies in the palm of your hand. This means that the only reasonable measurement is 19 mm, (& 8 cm, but that is only if you have really large hands). Therefore, (A) is your choice.
~
Answer:
<u />![\displaystyle \lim_{x \to 3} \frac{\sqrt{x + 1} - 2}{x - 3} = \boxed{ \frac{1}{4} }](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bx%20%5Cto%203%7D%20%5Cfrac%7B%5Csqrt%7Bx%20%2B%201%7D%20-%202%7D%7Bx%20-%203%7D%20%3D%20%5Cboxed%7B%20%5Cfrac%7B1%7D%7B4%7D%20%7D)
General Formulas and Concepts:
<u>Calculus</u>
Limits
Limit Rule [Variable Direct Substitution]:
![\displaystyle \lim_{x \to c} x = c](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bx%20%5Cto%20c%7D%20x%20%3D%20c)
Special Limit Rule [L’Hopital’s Rule]:
![\displaystyle \lim_{x \to c} \frac{f(x)}{g(x)} = \lim_{x \to c} \frac{f'(x)}{g'(x)}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bx%20%5Cto%20c%7D%20%5Cfrac%7Bf%28x%29%7D%7Bg%28x%29%7D%20%3D%20%5Clim_%7Bx%20%5Cto%20c%7D%20%5Cfrac%7Bf%27%28x%29%7D%7Bg%27%28x%29%7D)
Differentiation
- Derivatives
- Derivative Notation
Derivative Property [Addition/Subtraction]:
![\displaystyle \frac{d}{dx}[f(x) + g(x)] = \frac{d}{dx}[f(x)] + \frac{d}{dx}[g(x)]](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7Bd%7D%7Bdx%7D%5Bf%28x%29%20%2B%20g%28x%29%5D%20%3D%20%5Cfrac%7Bd%7D%7Bdx%7D%5Bf%28x%29%5D%20%2B%20%5Cfrac%7Bd%7D%7Bdx%7D%5Bg%28x%29%5D)
Derivative Rule [Basic Power Rule]:
- f(x) = cxⁿ
- f’(x) = c·nxⁿ⁻¹
Derivative Rule [Chain Rule]:
![\displaystyle \frac{d}{dx}[f(g(x))] =f'(g(x)) \cdot g'(x)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7Bd%7D%7Bdx%7D%5Bf%28g%28x%29%29%5D%20%3Df%27%28g%28x%29%29%20%5Ccdot%20g%27%28x%29)
Step-by-step explanation:
<u>Step 1: Define</u>
<em>Identify given limit</em>.
![\displaystyle \lim_{x \to 3} \frac{\sqrt{x + 1} - 2}{x - 3}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bx%20%5Cto%203%7D%20%5Cfrac%7B%5Csqrt%7Bx%20%2B%201%7D%20-%202%7D%7Bx%20-%203%7D)
<u>Step 2: Find Limit</u>
Let's start out by <em>directly</em> evaluating the limit:
- [Limit] Apply Limit Rule [Variable Direct Substitution]:
![\displaystyle \lim_{x \to 3} \frac{\sqrt{x + 1} - 2}{x - 3} = \frac{\sqrt{3 + 1} - 2}{3 - 3}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bx%20%5Cto%203%7D%20%5Cfrac%7B%5Csqrt%7Bx%20%2B%201%7D%20-%202%7D%7Bx%20-%203%7D%20%3D%20%5Cfrac%7B%5Csqrt%7B3%20%2B%201%7D%20-%202%7D%7B3%20-%203%7D)
- Evaluate:
![\displaystyle \begin{aligned}\lim_{x \to 3} \frac{\sqrt{x + 1} - 2}{x - 3} & = \frac{\sqrt{3 + 1} - 2}{3 - 3} \\& = \frac{0}{0} \leftarrow \\\end{aligned}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cbegin%7Baligned%7D%5Clim_%7Bx%20%5Cto%203%7D%20%5Cfrac%7B%5Csqrt%7Bx%20%2B%201%7D%20-%202%7D%7Bx%20-%203%7D%20%26%20%3D%20%5Cfrac%7B%5Csqrt%7B3%20%2B%201%7D%20-%202%7D%7B3%20-%203%7D%20%5C%5C%26%20%3D%20%5Cfrac%7B0%7D%7B0%7D%20%5Cleftarrow%20%5C%5C%5Cend%7Baligned%7D)
When we do evaluate the limit directly, we end up with an indeterminant form. We can now use L' Hopital's Rule to simply the limit:
- [Limit] Apply Limit Rule [L' Hopital's Rule]:
![\displaystyle \begin{aligned}\lim_{x \to 3} \frac{\sqrt{x + 1} - 2}{x - 3} & = \lim_{x \to 3} \frac{(\sqrt{x + 1} - 2)'}{(x - 3)'} \\\end{aligned}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cbegin%7Baligned%7D%5Clim_%7Bx%20%5Cto%203%7D%20%5Cfrac%7B%5Csqrt%7Bx%20%2B%201%7D%20-%202%7D%7Bx%20-%203%7D%20%26%20%3D%20%5Clim_%7Bx%20%5Cto%203%7D%20%5Cfrac%7B%28%5Csqrt%7Bx%20%2B%201%7D%20-%202%29%27%7D%7B%28x%20-%203%29%27%7D%20%5C%5C%5Cend%7Baligned%7D)
- [Limit] Differentiate [Derivative Rules and Properties]:
![\displaystyle \begin{aligned}\lim_{x \to 3} \frac{\sqrt{x + 1} - 2}{x - 3} & = \lim_{x \to 3} \frac{(\sqrt{x + 1} - 2)'}{(x - 3)'} \\& = \lim_{x \to 3} \frac{1}{2\sqrt{x + 1}} \leftarrow \\\end{aligned}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cbegin%7Baligned%7D%5Clim_%7Bx%20%5Cto%203%7D%20%5Cfrac%7B%5Csqrt%7Bx%20%2B%201%7D%20-%202%7D%7Bx%20-%203%7D%20%26%20%3D%20%5Clim_%7Bx%20%5Cto%203%7D%20%5Cfrac%7B%28%5Csqrt%7Bx%20%2B%201%7D%20-%202%29%27%7D%7B%28x%20-%203%29%27%7D%20%5C%5C%26%20%3D%20%5Clim_%7Bx%20%5Cto%203%7D%20%5Cfrac%7B1%7D%7B2%5Csqrt%7Bx%20%2B%201%7D%7D%20%5Cleftarrow%20%5C%5C%5Cend%7Baligned%7D)
- [Limit] Apply Limit Rule [Variable Direct Substitution]:
![\displaystyle \begin{aligned}\lim_{x \to 3} \frac{\sqrt{x + 1} - 2}{x - 3} & = \lim_{x \to 3} \frac{(\sqrt{x + 1} - 2)'}{(x - 3)'} \\& = \lim_{x \to 3} \frac{1}{2\sqrt{x + 1}} \\& = \frac{1}{2\sqrt{3 + 1}} \leftarrow \\\end{aligned}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cbegin%7Baligned%7D%5Clim_%7Bx%20%5Cto%203%7D%20%5Cfrac%7B%5Csqrt%7Bx%20%2B%201%7D%20-%202%7D%7Bx%20-%203%7D%20%26%20%3D%20%5Clim_%7Bx%20%5Cto%203%7D%20%5Cfrac%7B%28%5Csqrt%7Bx%20%2B%201%7D%20-%202%29%27%7D%7B%28x%20-%203%29%27%7D%20%5C%5C%26%20%3D%20%5Clim_%7Bx%20%5Cto%203%7D%20%5Cfrac%7B1%7D%7B2%5Csqrt%7Bx%20%2B%201%7D%7D%20%5C%5C%26%20%3D%20%5Cfrac%7B1%7D%7B2%5Csqrt%7B3%20%2B%201%7D%7D%20%5Cleftarrow%20%5C%5C%5Cend%7Baligned%7D)
- Evaluate:
![\displaystyle \begin{aligned}\lim_{x \to 3} \frac{\sqrt{x + 1} - 2}{x - 3} & = \lim_{x \to 3} \frac{(\sqrt{x + 1} - 2)'}{(x - 3)'} \\& = \lim_{x \to 3} \frac{1}{2\sqrt{x + 1}} \\& = \frac{1}{2\sqrt{3 + 1}} \\& = \boxed{ \frac{1}{4} } \\\end{aligned}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cbegin%7Baligned%7D%5Clim_%7Bx%20%5Cto%203%7D%20%5Cfrac%7B%5Csqrt%7Bx%20%2B%201%7D%20-%202%7D%7Bx%20-%203%7D%20%26%20%3D%20%5Clim_%7Bx%20%5Cto%203%7D%20%5Cfrac%7B%28%5Csqrt%7Bx%20%2B%201%7D%20-%202%29%27%7D%7B%28x%20-%203%29%27%7D%20%5C%5C%26%20%3D%20%5Clim_%7Bx%20%5Cto%203%7D%20%5Cfrac%7B1%7D%7B2%5Csqrt%7Bx%20%2B%201%7D%7D%20%5C%5C%26%20%3D%20%5Cfrac%7B1%7D%7B2%5Csqrt%7B3%20%2B%201%7D%7D%20%5C%5C%26%20%3D%20%5Cboxed%7B%20%5Cfrac%7B1%7D%7B4%7D%20%7D%20%5C%5C%5Cend%7Baligned%7D)
∴ we have <em>evaluated</em> the given limit.
___
Learn more about limits: brainly.com/question/27807253
Learn more about Calculus: brainly.com/question/27805589
___
Topic: AP Calculus AB/BC (Calculus I/I + II)
Unit: Limits